Characteristics of Bread with The Substitution of Fermented Purple Yam Flour (Dioscorea alata) - Ulyarti Ulyarti; Mursyid Mursyid; Lavlinesia Lavlinesia; Iqbal Ridho Juliandri; Nazarudin Nazarudin (agriTECH, 2023)
Fermented purple yam flour is known to have high swelling power, which is capable of improving its ability as a substitute for wheat flour in bread production. Therefore, this study aimed to determine the effect of the substitution of wheat flour with fermented purple yam flour (FF), at 0%, 10%, 15%, 20%, 25%, and 30% concentrations on the physical, chemical, and sensory characteristics of bread. The result showed that FF concentration has no significant effect on the moisture content, specific loaf volume, hedonic aroma, and taste but significantly affected porosity, anthocyanin content, antioxidant activity, hedonic color, texture, and overall acceptance of the bread. Furthermore, the best treatment obtained was at the 25% substitution level, which produced bread with 29.30% moisture content, 27.18% porosity, 3.06 cm 3 /g specific loaf volume, and 5.30 mg/g anthocyanin. It also produced 61.03% antioxidant activity, color 3.88, texture 4.00, taste 3.92, and overall acceptance 4.00 (Likes). The maximum substitution rate of fermented purple yam flour was 25%.